Everyman's Jurisprudence: In Search of a Common Sense Theory of Legal Justification - Brian V. Faller (Washington University Law Quarterly, 1985)
Judges and lawyers daily confront one of the most vexing problems of modern jurisprudence: they must determine whether a given legal rule or an interpretation of it is legally correct. To make this determination they consider a variety of factors such as the literal meaning of the rule, the intent of the rule's creator, the consequences that one rule or interpretation would have as opposed to another, and the interpretations that courts have given to the rule or to a similar rule. Yet, even with this guidance, they are often hard put to justify their assertion that a given rule reflects a correct weighing of these factors. In order to supply such justification, it is necessary to have a theory of legal justification. This article develops a theory of legal justification, the Value Structure Theory (VST). VST asserts that our legal system is essentially a complex value structure and that the correctness of any given legal standard is determined by its coherence with that value structure. The purpose of this article is to show how VST can help us clarify which legal rules apply in concrete cases. Section I, the General Theory, examines the concept of legal values and the hierarchical relationship between these values and legal rules. Section II, the Specific Theory, brings the General Theory to the level of concrete application. It develops an account of the considerations that determine whether a given rule best reflects the existing order of legal values. This account forms the basis for an outline of the relevant factors that judges and lawyers should weigh in determining the appropriateness of creating a new legal standard.
Keywords: Jurisprudence